LES of Fire Plumes Subjected to Crosswind: The Influence of Wind Profile and Terrain Slope on the Formation of Vertical Structures - Bruno A. C. Barata; José C. F. Pereira (Fire)
This study investigates the behaviour of plumes from massive fires subjected to crosswinds, focusing on how varying wind profiles and terrain characteristics influence the formation of coherent vortical structures, particularly wake vortices, and the smoke distribution in the near-fire region. Large Eddy Simulations (LES) were employed to model the interaction between the plume, generated by a rectangular fireline with an intensity of <semantics>40<mspace width="0.166667em"></mspace>MW/m</semantics>, and the crosswind. Upon the consideration of several wind intensities (from 5 to <semantics>10<mspace width="0.166667em"></mspace>m/s</semantics>) and vertical distributions, it was verified that only for relatively low average wind velocities was there significant lateral entrainment to the flame, which promoted the formation of vertical vortical structures. Depending on the vertical distribution of the wind, different mechanisms can play a role in the formation of these structures, with a larger number of mechanisms involved for the cases where there is very low near-wall wind momentum, typical of large vegetation regions. The slope of the terrain (from <semantics>−20∘</semantics> to <semantics>+20∘</semantics>) plays a role in these relations since it affects the fire plume inclination and, consequently, the entrainment process. These structures are more likely to appear in downslope terrains.